Foreign Aid And Democracy: An Analysis Of The Us Aid To Pakistan In Post-Cold War Era (1999-2020) - Said Wahab; Dr. Sajjad Ali Khan; Tahir Mahmood; Dr. Ahmad Ali; Dr. Abdul Shakoor (Elementary Education Online, 2023)
On the heels of the World War II, President Harry Truman unveiled the Marshal Plan (MP) in anticipation to cope with the ravages of the War through reconstructing the war-torn European states. The Marshal Plan entailed the disbursement of a colossal amount of foreign aid in (US dollars). Apart from development and reconstruction, foreign aid under the MP was also propelled to foster democratic values and to contain the spread of Communism both in Europe as well as the rest of the World. Since then, foreign aid has served as the linchpin of the United States of America’s foreign policy to promote a verity of goals, let alone the promotion of democracy. The proposed study is interested in exploring the relationship between foreign aid and democracy through an analysis of the effects of USAID’s financial assistance on democracy promotion in Pakistan. Secondary data will be retrieved from secondary sources such as government and non-governmental reports, articles, newspapers and books etc. the findings adumbrate that despite receiving billions of US dollars from the United States of America, the form of government in Pakistan can best be described as something of a hybrid sort. The findings suggest that as opposed to the theoretical debates underpinning the relationship between foreign aid and democracy, foreign aid may only foster democratic values under specific circumstances.